A REVIEW ON SURFACTANTS AS EDGE ACTIVATORS IN ULTRADEFORMABLE VESICLES FOR ENHANCED SKIN DELIVERY. - LEENA JACOB,; ANOOP KR, (International Journal of Pharma and Bio Sciences, 2013)
Edge activators are bilayer softening component, such as biocompatible surfactant in to which an amphiphilic drug is added to increase lipid bilayer flexibility and permeability. Many drugs having severe gastro-intestinal toxicity can be successfully delivered transdermally, but threshold barrier that is stratum corneum is the main limitation. An approach for enhancing the drug flux through the skin is by the chemical interaction of surfactant and solubilisation of the lipid in stratum corneum and enhances the penetration of many drugs. This article insights the mechanism of interaction of edge activators (surfactant) with lipid bilayer, influence of edge activators on vesicular morphology, entrapment efficiency, zeta potential, drug release, deformability, skin permeation and skin deposition. This article also reviews measurement of permeation capacity of surfactants, the application of deformable vesicles containing edge activators in transdermal delivery of various biological.